33. FIRST AID KNOWLEDGE DEFICITS AND EDUCATIONAL DEMANDS AMONG STUDENTS AT HUE UNIVERSITY: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess first aid knowledge, attitudes, and training needs among university students at Hue University.Methods: A cross-sectional descriptive study was conducted from October 2024 to March 2025 with 217 students participating. Data were collected using a self-administered questionnaire consisting of four parts: demographics, knowledge, attitudes, and training needs. Data were analyzed using SPSS 20.0.Results: Among participants, 61.3% had never received first aid training, and only 20.3% had participated in first aid situations. The average knowledge score was 30.80 ± 6.79 out of 41. While basic first aid knowledge was relatively high, more complex topics—such as spinal or head trauma and snake bites—had low correct response rates. A total of 75.6% were willing to provide first aid if needed, though many expressed concerns about causing harm or legal consequences. Notably, 98% showed interest in participating in first aid training programs.Conclusion: Students demonstrated positive attitudes and strong demand for first aid education, yet significant knowledge gaps remain. Educational institutions should integrate structured first aid training into curricula to enhance students’ emergency response capabilities.
Keywords: First aid; knowledge; attitude; and training needs